Oportunidades de las Pymes del sector textil de Colombia en el comercio electrónico en tiempos de covid-19. (2021)
What will be presented in this work is the analysis of the opportunities of SMEs in Colombia's textile sector in covid-19 times e-commerce, taking into account characteristics, variables and possible factors that may favor or affect such implementation. The methodology used for the preparation of the document was descriptive in nature, because information was collected from different academic databases, as well as several government agencies and other digital resources such as articles or news.